Tingkat Pencapaian Mahasiswa Melalui Isomorfik Tipe B Pada Topik Satuan - Sudarto Sudarto; Abd. Kadir A (Departement of Mathematics Education, 2023)
This research is a pre-experimental research conducted to find out the subject knowledge abilities of PGSD FIP UNM Campus VI Bone students who are programming the Elementary Science Basic Concepts course in the even semester of the 2021/2022 academic year on the topic of Units through a type B isomorphic test. The birth of a profile/picture the ability of subject knowledge of PGSD FIP UNM Campus VI Bone students who are programming the Elementary Science Basic Concepts course in the even semester of the 2021/2022 academic year on the topic of Units through the type B isomorphic test is the target to be achieved. To achieve this target, the researcher explored the subject knowledge abilities of the students who were the target subjects by giving a type B isomorphic test. The test was in the form of a written test. The research subjects were PGSD FIP UNM Campus VI Bone students who were programming the Science Basic Concepts Course in the Even Semester of the 2021/2022 Academic Year. Data collection is done by recording test results. The analysis technique uses descriptive analysis. The results showed that students (respondents) who scored in the